Safety and short‑term outcomes of a modified tubular esophagogastrostomy versus double tract reconstruction after proximal gastrectomy: a propensity score matching analysis - Chaoyang Zhang; Kaixing Wang; Zhidong Zhang; Xuefeng Zhao; Bin Yao; Weishuai Zhang (BMC Cancer)
Abstract Objective To comparatively evaluate the short-term clinical efficacy and quality of life (QoL) between modified tubular esophagogastrostomy (mTEG) and double tract reconstruction (DTR) following proximal gastrectomy (PG), aiming to establish evidence-based recommendations for reconstruction method selection. Methods The mTEG technique involved three essential steps: 1) tubular reconstruction of gastric remnant, 2) 3-cm artificial gastric fornix creation, and 3) His angle sharpening with posterior mediastinal fixation. This retrospective study included 288 PG patients (2021–2024). Propensity score matching (1:1, caliper = 0.03) balanced baseline characteristics, and thirty-three matched pairs were analyzed. Outcomes encompassed operative metrics, postoperative complications (Clavien-Dindo ≥ II), nutritional status (prealbumin, albumin, hemoglobin, BMI at 1/3/6 months), and QoL (EORTC QLQ-STO22 at 6 months). Results The mTEG group demonstrated shorter median operative time (163.7 vs 247.9 min, p < 0.001) and postoperative hospitalization (8.3 vs 9.9 days, p = 0.001). Intraoperative outcomes including blood loss and lymph node yield were comparable. Early complications (≤ 30 days) occurred exclusively in the DTR group (4 cases: 2 anastomotic leakage, 1chylous leakage and 1 pulmonary related). complication rates showed no statistical difference (p > 0.05). Endoscopic findings demonstrated comparable incidence of reflux esophagitis in Los Angeles Grade B or higher (11.1% vs 4.5%, p = 0.457). Nutritional parameters and QoL scores remained equivalent between groups at all timepoints (p > 0.05). Conclusion mTEG represents a technically optimized reconstruction method that achieves equivalent nutritional preservation and reflux prevention compared to DTR, while offering distinct advantages in surgical efficiency and postoperative recovery. These findings support mTEG as a viable reconstruction option for PG patients.